E-cognitive scaffolding: does it have an impact on the English grammar competencies of middle school underachieving students?. (2nd January 2021) - Abdelaziz, Hamdy A.; Al Zehmi, Owaisha
ABSTRACT: This research aimed to design e-activities based on cognitive scaffolding and measure their impact on underachieving learners' grammar competencies in middle schools. The focus was to utilise technology tools in providing underachieving learners with the support necessary to help them improve their usage of English grammar. A set of electronic activities based on cognitive scaffolding principles and techniques, which included six basic grammar lessons, was designed and assembled in a free host website. The quasi-experimental research was designed to measure the impact of the e-activities that were based on cognitive scaffolding on learners' performance. Forty seven learners were involved in the study. Additionally, a data analysis technique, analysis of covariance (ANCOVA), was used to compare the results of the control group and the experimental group. The findings of the study showed significant differences. The differences in this study were in favour of the experimental group.